Speculation-driven business cycles - Saki Bigio; Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2019)
Speculation, in the spirit of Harrison and Kreps [1978], is introduced into a standard real business cycle model. Investors (speculators) hold heterogeneous beliefs about firm growth. Firm ownership, and thus, the firm's discount factor varies with waves of optimism and leverage. These waves ripple into firm investments in hours. The firm's discount discount factor links the equity premium and labor volatility puzzles. We obtain an upper bound to the amplification that can be generated by speculation for any model of beliefs - a factor of 1.5. A calibration based on diagnostic beliefs amplifies hours volatility by a factor of 1.15 and produces a bubble component of 20 percent.
Keywords: D84; E32; E44; E71; G41; 330; Heterogeneous Beliefs; Business Cycles; Asset Prices; Speculation; Bubbles